Analogous Mixed Matrix Membranes with Self‐Assembled Interface Pathways. Issue 11 (27th January 2021) - Dou, Haozhen; Xu, Mi; Wang, Baoyu; Zhang, Zhen; Luo, Dan; Shi, Benbing; Wen, Guobin; Mousavi, Mahboubeh; Yu, Aiping; Bai, Zhengyu; Jiang, Zhongyi; Chen, Zhongwei
Abstract: The implementation of mixed matrix membranes (MMMs) for sub‐angstrom scale gas separations remains a grand challenge. Herein, a series of analogous mixed matrix membrane (AMMMs) were constructed via molecular‐level hybridization by utilizing a reactive ionic liquid (RIL) as the continuous phase and graphene quantum dots (GQD) as nanofiller for sub‐angstrom scale ethylene/ethane (0.416 nm/0.443 nm) separation. With a small number of GQDs (3.5 wt%) embedded in GQD/RIL AMMMs, ethylene permeability soared by 3.1‐fold, and ethylene/ethane selectivity simultaneously boosted by nearly 60 % and reached up to 99.5, which outperformed most previously reported state‐of‐the‐art membranes. Importantly, the interfacial pathway structure was visualized and their self‐assembly mechanism was revealed, where the non‐covalent interactions between RIL and GQDs induced the local arrangement of IL chains to self‐assemble into plenty of compact and superfast interfacial pathways, contributing to the combination of superhigh permeability and selectivity. Abstract : A series of analogous mixed matrix membranes with self‐assembled interface pathways were constructed via molecular‐level hybridization by utilizing a reactive ionic liquid (RIL) as the continuous phase and graphene quantum dots (GQD) as nanofiller for sub‐angstrom‐scale ethylene/ethane (0.416 nm/0.443 nm) separation. Importantly, the interfacial pathway structure was visualized and the self‐assembly mechanism was revealed.